2024
DOI: 10.1002/wjs.12069
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional survey on surgeon retention in the COSECSA region after specialist training: Have things changed?

Abebe Bekele,
Barnabas Tobi Alayande,
Jules Iradukunda
et al.

Abstract: BackgroundIncreasing surgical specialist workforce density in sub‐Saharan Africa is essential for improving access to surgical care. However, out‐migration creates a significant challenge to attaining provider targets. We aimed to determine the rates and trends of retention of surgeons in the College of Surgeons of East Central and Southern Africa (COSECSA) regions.MethodologyAn online, web‐based survey was distributed to COSECSA surgeons who graduated from 2004 to 2020. Current practice and migration patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Discussions around the problems of health workforce brain drain and sustainable solutions for retention and reversal of the trend have been topical for decades. The report by Bekele et al 1 on retention of COSECSA trained surgeons is quite timely and informative, at a time of increasing focus on increasing access to safe, timely and quality surgical care in sub-Saharan Africa (SSA). Coming against the background of recent large migration of highly trained surgical workforce from SSA, their findings provide some encouragement and comfort.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Discussions around the problems of health workforce brain drain and sustainable solutions for retention and reversal of the trend have been topical for decades. The report by Bekele et al 1 on retention of COSECSA trained surgeons is quite timely and informative, at a time of increasing focus on increasing access to safe, timely and quality surgical care in sub-Saharan Africa (SSA). Coming against the background of recent large migration of highly trained surgical workforce from SSA, their findings provide some encouragement and comfort.…”
mentioning
confidence: 99%
“…Bekele et al 1 report that 50% of the retained surgeons practiced in urban capitals and only 8.5% at district hospitals. A previous report from Nigeria, a WACS region country, found that 74% of surgical trainees preferred to work in tertiary hospitals which are located in urban areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation